High-hardness single crystal niobium and preparation method thereof

By annealing, pretreatment, and impact loading, martensitic phase transformation is induced in single-crystal niobium, solving the problem of improving the hardness of single-crystal niobium and realizing the preparation of single-crystal niobium with high hardness and integrity. This method is applicable to single-crystal niobium materials with various crystal orientations.

CN119392378AActive Publication Date: 2025-02-07INST OF MATERIALS HENAN ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411573414.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing technologies cannot effectively improve the hardness of single-crystal niobium, making it prone to deformation under external loads, which affects structural integrity and service safety.

Method used

By annealing, pretreatment, and impact loading, a martensitic phase transformation is induced in single-crystal niobium, resulting in a high-hardness single-crystal niobium microstructure. The martensite extends along... <110> The crystal orientations are uniformly distributed, with a volume fraction of 61–73%.

Benefits of technology

It significantly improves the hardness of single-crystal niobium, achieving high hardness and integrity of the material. The process is simple, low-cost, and environmentally friendly, and is suitable for single-crystal niobium materials with any crystal orientation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392378A_ABST
    Figure CN119392378A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plastic deformation preparation of metal materials, and provides high-hardness single crystal niobium and a preparation method thereof, and the martensite content in a metallographic structure of the high-hardness single crystal niobium is 61-73%. The preparation process comprises the procedures of annealing, pretreatment and deformation impact on single crystal niobium, annealing parameters and the impact strain rate are accurately regulated and controlled, so that the single crystal niobium is subjected to structural phase change to introduce a high-hardness martensite structure, meanwhile, impact cracks are effectively avoided, and finally the crack-free high-hardness single crystal niobium is obtained. The method provided by the invention is simple in process flow, high in efficiency, low in cost, green, low-carbon and pollution-free, can remarkably improve the hardness of the single crystal niobium, and is suitable for the single crystal raw material niobium in any crystal orientation. The result of the embodiment shows that the hardness of single crystal niobium with the crystal orientation of [100], [110] and [111] is respectively improved by 24%, 52% and 42% after the single crystal niobium is subjected to impact deformation by the method disclosed by the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic deformation preparation of metal materials, and in particular to a high-hardness single crystal niobium and a preparation method thereof. Background Art

[0002] Niobium (Nb) metal has excellent properties such as high plasticity, superconductivity and magnetic anisotropy, and is widely used in low-temperature superconductivity, deep-sea polar, nuclear magnetic resonance and other fields. Especially with the rapid development of superconducting high-frequency technology in recent decades, major accelerator devices in the world have generally used superconducting high-frequency cavities made of pure niobium to accelerate various charged particles. Compared with traditional polycrystalline niobium, single-crystalline niobium does not contain grain boundaries (interface defects usually increase the scattering effect on electrons), and its electrical, magnetic and other functional properties are more excellent. However, as a functional-structural integrated material, the application requirements for single-crystalline niobium are not only limited to functional properties, but also emphasize its mechanical properties such as hardness. Because single-crystalline niobium is relatively soft in texture, it is easy to deform under the action of external loads, which greatly affects its structure and service safety.

[0003] At present, the main strategies to improve the hardness of metals include solid solution / precipitation strengthening, surface strengthening, and phase change strengthening. The hardness of the material itself can be improved by adding alloying elements (such as C, Si, Mn, etc.) through solid solution strengthening or precipitation strengthening. However, this method has a relatively limited improvement and usually seriously affects the functional properties of the material. Surface strengthening is a gas carburizing / nitriding process under high temperature or vacuum environment. Due to the harsh reaction conditions, it is more suitable for small-scale applications. Phase change strengthening usually involves heat treatment of metal materials (such as quenching) to induce structural phase changes (such as martensitic transformation) to achieve strengthening. The operation is relatively simple, but it cannot be directly applied to pure metal materials with stable structures.

[0004] In view of this, there is an urgent need to provide a new method that is simple to operate and can effectively improve the hardness of single crystal niobium. Summary of the invention

[0005] In view of the above problems of single crystal niobium, the present invention aims to provide a high-hardness single crystal niobium with a simple preparation process and complete crack-free. The single crystal niobium has a high martensite content (61-73%) in its structure, which can significantly improve the hardness of the single crystal niobium and has good industrial application prospects.

[0006] The specific technical solutions provided by the present invention are as follows:

[0007] A method for preparing high-hardness single-crystal niobium comprises the following steps:

[0008] (1) Annealing the single crystal niobium;

[0009] (2) pretreating the annealed single crystal niobium;

[0010] (3) impact loading the pretreated single crystal niobium to obtain the high-hardness single crystal niobium; the metallographic structure of the high-hardness single crystal niobium includes martensite in the shape of a double convex lens, and the martensite is <110> The crystal orientation groups are evenly distributed in single crystal niobium; the volume fraction of martensite is 61-73%.

[0011] Preferably, in step (1), the annealing conditions are: keeping warm at 600-1200°C for 6-8h; further preferably, the annealing temperature is 800-1000°C to eliminate defect structures such as dislocations inside the material, which is conducive to the subsequent martensitic phase transformation.

[0012] Preferably, in step (2), the pretreatment method is to grind, polish and ultrasonically clean the annealed single crystal niobium in sequence; the grinding is preferably: coarse grinding and fine grinding are performed successively with metallographic sandpaper with particle sizes of #180, #500 and #800; the polishing is preferably: polishing the sample to a mirror surface level with a diamond polishing spray with a particle size of W2; the cleaning agent used in the ultrasonic cleaning is preferably alcohol, the ultrasonic power is preferably 200W, and the ultrasonic time is preferably 5min; the above parameters are to ensure the removal of oil stains on the surface of the single crystal niobium and avoid uneven deformation of the sample.

[0013] Preferably, in step (3), the strain rate of the impact is 1×10 3 ~6×10 3 s -1 , the temperature is room temperature.

[0014] Preferably, in step (3), the device used for the impact is a Hopkinson pressure bar device, which has good impact stress uniformity and a large measurable strain rate range, so as to effectively impact deform the single crystal niobium at the required impact rate.

[0015] Further preferably, the end face size of the single crystal niobium is smaller than the end face sizes of the incident rod and the transmission rod in the Hopkinson pressure rod device.

[0016] Preferably, the crystal orientation of the single crystal niobium is

[100] ,

[110] or

[111] ; and the purity of the single crystal niobium is not less than 99.9%.

[0017] Preferably, the surface roughness of the single crystal niobium is less than 0.03 μm; and the roughness of both end surfaces of the single crystal niobium is less than 0.02.

[0018] Preferably, the C content in the single crystal niobium is 25-88 ppm, the H content is less than 1 ppm, the O content is 15-230 ppm, the N content is less than 5 ppm, and the Ag content is less than 0.9 ppm.

[0019] Further preferably, the single crystal niobium before impact has a body-centered cubic (BCC) structure; the present invention has no special requirements on the source of the single crystal niobium, and commercially available single crystal niobium can be used.

[0020] The beneficial effects of the present invention are:

[0021] (1) The high-hardness single-crystal niobium involved in the present invention is obtained by subjecting commercially available single-crystal niobium to an impact deformation process to induce a martensitic phase transformation. By precisely controlling the annealing parameters and the impact strain rate, a significant improvement in the hardness of the material is achieved, and finally a complete, crack-free, high-hardness single-crystal niobium is obtained.

[0022] (2) The impact deformation process is used to induce martensitic phase transformation. This process is simple, efficient, low-cost, green, low-carbon and pollution-free.

[0023] (3) This method is applicable to single crystal raw materials of niobium with any crystal orientation, and is expected to be extended to niobium-based single crystals and polycrystalline alloys, such as niobium-titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The hardness indentation profiles of single crystal niobium with

[100] crystal orientation at five different positions (corresponding to different indentation depths) before and after impact in Example 1, where the top one is before impact and the bottom one is after impact;

[0025] Figure 2 The hardness indentation diagrams of single crystal niobium with

[110] crystal orientation at five different positions (corresponding to different indentation depths) before and after impact in Example 2, where the top one is before impact and the bottom one is after impact;

[0026] Figure 3 The hardness indentation diagrams of single crystal niobium with

[111] crystal orientation at five different positions (corresponding to different indentation depths) before and after impact in Example 3, where the top one is before impact and the bottom one is after impact;

[0027] Figure 4 The SEM morphology of the martensite on the surface after the single crystal niobium in three crystal directions was corroded after impact deformation in Examples 1 to 3;

[0028] Figure 5 This is the SEM morphology of the single crystal niobium after impact deformation in Comparative Example 4;

[0029] Figure 6 These are the XRD characterization results of single crystal niobium in three crystal orientations before and after impact in Examples 1 to 3. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0031] Example 1

[0032] The single crystal niobium used in this embodiment has a crystal orientation of

[100] and a crystal orientation deviation of <1°; it is disc-shaped, has a surface roughness of <0.03 μm, a diameter of 10 mm, a thickness of 4 mm, an unevenness of the two end surfaces of the sample of less than 0.02, a purity of more than 99%, and impurity element contents as follows: C 25 ppm, H<1 ppm, O 15 ppm, N<5 ppm, and Ag<0.9 ppm.

[0033] The single crystal niobium sample was annealed at 1000℃ for 6h, and then ground, polished and ultrasonically cleaned for use. At room temperature, the single crystal niobium was subjected to an impact test using a Hopkinson pressure bar device, as follows: the rod system was adjusted based on the axis of the launch tube, and the front and rear center brackets were adjusted using a height gauge, a level gauge, a micrometer, etc. to make the rod end face fit closely with the bullet end face. Stainless steel gaskets were added between the sample and the incident rod end face, as well as between the sample and the transmission rod end face, and a small amount of vaseline was added between the gasket and the rod. Bottled high-pressure nitrogen and high-pressure air were used, and the launch tube vent valve was unscrewed to push the bullet into the appropriate position with a soft rod, and the impact strain rate was controlled at 1×10 3 s -1 The impacted sample was separated from the stainless steel gasket, and the sample was removed, rinsed and machined to obtain high-hardness single crystal niobium.

[0034] Example 2

[0035] The single crystal niobium used in this embodiment has a crystal orientation of

[110] and a crystal orientation deviation of <1°; it is disc-shaped, has a surface roughness of <0.03 μm, a diameter of 10 mm, a thickness of 4 mm, an unevenness of the two end surfaces of the sample of less than 0.02, a purity of more than 99%, and impurity element contents as follows: C 25 ppm, H<1 ppm, O 15 ppm, N<5 ppm, Ag<0.9 ppm.

[0036] The operation method of the impact test is the same as that of Example 1.

[0037] Example 3

[0038] The single crystal niobium used in this embodiment has a crystal orientation of

[111] and a crystal orientation deviation of <1°; it is disc-shaped, has a surface roughness of <0.03 μm, a diameter of 10 mm, a thickness of 4 mm, an unevenness of the two end surfaces of the sample of less than 0.02, a purity of more than 99%, and impurity element contents as follows: C 25 ppm, H<1 ppm, O 15 ppm, N<5 ppm, Ag<0.9 ppm.

[0039] The operation method of the impact test is the same as that of Example 1.

[0040] Comparative Example 1

[0041] The single crystal niobium used in this embodiment has a crystal orientation of

[110] and is prepared by referring to the preparation steps in Example 2, except that it is not annealed.

[0042] Comparative Example 2

[0043] The single crystal niobium used in this embodiment has a crystal orientation of

[110] and is prepared by referring to the preparation steps in Example 2, except that the annealing temperature is 400°C.

[0044] Comparative Example 3

[0045] The single crystal niobium used in this embodiment has a crystal orientation of

[110] and is prepared according to the preparation steps in Example 2, except that the impact strain rate is 1×10 2 s -1 .

[0046] Comparative Example 4

[0047] The single crystal niobium used in this embodiment has a crystal orientation of

[110] and is prepared according to the preparation steps in Example 2, except that the impact strain rate is 1×10 4 s -1 .

[0048] Test Case

[0049] 1. Hardness test

[0050] The hardness of single crystal niobium before and after impact in Examples 1 to 3 and Comparative Examples 1 to 4 was tested. During the test, 5 different positions were selected for each sample. The indentation depths during the test at the 5 positions were 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm and 1.8 mm, respectively, to test the hardness of the sample at different positions and depths. The test results are shown in Tables 1 to 5.

[0051] Table 1 Hardness of

[100] single crystal niobium before and after impact in Example 1

[0052]

[0053]

[0054] Table 2 Hardness of

[110] single crystal niobium before and after impact in Example 2

[0055] Location Depth(mm) Hardness before impact (HV) Hardness after impact (HV) 1 1.00 89.4 132.4 2 1.20 88.1 135.5 3 1.40 86.1 146.3 4 1.60 87.1 126.4 5 1.80 88.6 126.7

[0056] Table 3 Hardness of

[111] single crystal niobium before and after impact in Example 3

[0057] Location Depth(mm) Hardness before impact (HV) Hardness after impact (HV) 1 1.00 77.2 108.2 2 1.20 76.5 107.5 3 1.40 78.6 112.1 4 1.60 74.6 103.8 5 1.80 76.2 111.1

[0058] According to Tables 1 to 3, it can be seen that the hardness of single crystal niobium with different orientations at different positions in Examples 1 to 3 is significantly improved after impact. Figure 1 to Figure 3 It can be seen that the hardness indentation profile of single crystal niobium that undergoes martensitic transformation after impact is clear, and the profile morphology along different depths is basically consistent, indicating that the martensite is evenly distributed inside the sample. Combining Examples 1 to 3, it is shown that this method is universal for single crystal raw material niobium of any crystal orientation.

[0059] Table 4 Comparison of the effect of different annealing conditions on the hardness improvement of

[110] single crystal niobium in Example 2 and Comparative Examples 1-2

[0060]

[0061] According to Table 4, it can be seen that controlling the annealing conditions within the scope of the present invention can effectively increase the hardness of single crystal niobium. In Comparative Examples 1 and 2, when no annealing or a lower annealing temperature (400°C) is used, defects such as dislocations inside the material are not fully eliminated, resulting in competition with the martensitic phase transformation during the subsequent impact process, and the martensitic phase transformation is not sufficient, which has a limited effect on improving the hardness.

[0062] Table 5 Comparison of the effect of different impact rates on the hardness improvement of

[110] single crystal niobium in Example 2 and Comparative Examples 3-4

[0063]

[0064] According to Table 5, it can be seen that controlling the impact strain rate within the range of the present invention can effectively increase the hardness of single crystal niobium. In Comparative Example 3, a lower impact strain rate (1×10 2 s -1 ), which is insufficient to drive the martensitic transformation, resulting in a significant decrease in the hardness increase rate compared with Example 2. In Comparative Example 4, at a higher impact strain rate (1×10 4 s -1 ), a large number of microcracks were generated inside the sample, and it could not be used further. Based on Comparative Examples 3 to 4, it can be seen that the martensitic phase transformation is sensitive to the impact strain rate. By controlling the strain rate within the range of the present invention, a complete, crack-free, high-hardness single crystal niobium can be obtained.

[0065] 2. Characterization of martensite morphology

[0066] The SEM morphology of the martensite on the surface after the three crystal orientation single crystal niobium is impact deformed in Examples 1 to 3 is as follows: Figure 4 As shown. Figure 4 It can be seen that a large amount of martensite appears in single crystal niobium with

[100] ,

[110] and

[111] directions after impact.

[0067] The SEM image of the single crystal niobium after impact deformation in Comparative Example 4 is as follows: Figure 5 As shown. Figure 5 It can be seen that cracks appear on the surface of single crystal niobium after impact deformation. This is because a higher strain rate (1×10 4 s -1 ) impact, inducing a large amount of martensite to form rapidly and collide with each other, resulting in a large number of impact cracks in the sample, making it unusable for further use.

[0068] 3. XRD characterization

[0069] The XRD test results of the three single crystal niobium with different crystal orientations before and after impact in Examples 1 to 3 are as follows: Figure 6 As shown. Figure 6 It can be seen that single crystal niobium in the

[100] ,

[110] and

[111] directions showed strong martensitic diffraction peaks after impact, indicating that a large amount of martensitic structure was produced during the impact process.

[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing high-hardness single crystal niobium, characterized in that: The following steps are involved: (1) Annealing the single crystal niobium; (2) pretreating the annealed single crystal niobium; (3) impact loading the pretreated single crystal niobium to obtain the high-hardness single crystal niobium; the metallographic structure of the high-hardness single crystal niobium includes martensite in the shape of a double convex lens, and the martensite is <110> The crystal orientation groups are evenly distributed in single crystal niobium; the volume fraction of martensite is 61-73%.

2. The preparation method according to claim 1, characterized in that: In step (1), the annealing treatment conditions are: 600-1200° C., and the insulation time is 6-8 hours.

3. The preparation method according to claim 1, characterized in that: In step (2), the pretreatment steps are: grinding, ultrasonic cleaning and polishing.

4. The preparation method according to claim 1, characterized in that: In step (3), the strain rate of the impact is 1×10 3 ~6×10 3 s -1 , the temperature is room temperature.

5. The preparation method according to claim 1, characterized in that: In step (3), the device used for the impact is a Hopkinson pressure bar device.

6. The preparation method according to claim 5, characterized in that: The end face size of the single crystal niobium is smaller than the end face sizes of the incident rod and the transmission rod in the Hopkinson pressure rod device.

7. The preparation method according to claim 1, characterized in that: The C content of the single crystal niobium is 25-88ppm, the H content is less than 1ppm, the O content is 15-230ppm, the N content is less than 5ppm, and the Ag content is less than 0.9ppm.

8. The preparation method according to claim 1, characterized in that: The crystal orientation of the single crystal niobium is [100], [110] or [111]; the purity of the single crystal niobium is not less than 99.9%.

9. The preparation method according to claim 1, characterized in that: The surface roughness of the single crystal niobium is less than 0.03 μm; the roughness of both end surfaces of the single crystal niobium is less than 0.02.

Citation Information

Patent Citations

  • Micro-carbon high-strength deep-punching steel with niobium and chromium, and preparation method thereof

    CN110484697A

  • Method for improving room-temperature mechanical property of molybdenum-niobium single crystal

    CN115787063A

  • Laser shock peening method for nickel-based precipitation-hardening single-crystal high-temperature alloy

    CN116179801A

  • Niobium-containing high-strength dual-phase steel as well as preparation method and application thereof

    CN116732297A

  • High strength cold-rolled steel sheet and method for manufacturing the same

    KR1020130046966A